PANJANG DAN BOBOT SALURAN REPRODUKSI PUYUH BETINA (Coturnix coturnix japonica) SETELAH PEMBERIAN TEPUNG KUNYIT (Curcuma longa L.) - Isna Handayani; Silvana Tana; Tyas Rini Saraswati (Jurnal Akademika Biologi, 2013)
Quail (Coturnix coturnix japonica) is a kind of fowl that produces eggs. The protein and fat in quail eggs that is higher than other eggs has become the reason why quail eggs has been chosen to fulfill the needs of nutrition. Quail breed and grow in 42 days. This study was intended to measure the lenght and weight of quail reproductive tract after given some amount of turmeric powder. The experiment was used 60 quail that was divided into three groups 4 different treatments in 5 repetition. The treatment was started when quail was 3 week-old during a month. The parameter in this research was the lenght and weight of reproductive tract using Complete Random Design. Data obtained was then analyzed using Analysis of Variant (ANOVA). The result shows was not differences in the lenght of reproductive tract, the weight of reproductive tract, food consumption and water consumption. The conclusion of the research is that turmeric powder (Curcuma longa L.) has not been proven to develop the cells in quail reproductive tract.    Keywords : Turmeric powder, quail (Coturnix coturnix japonica), lenght and weight of reproductive tract.